Jetztzeit. - Durham, Jimmie; Schmidt, Burghart; Cameron, Dan; Kunsthalle Wien; De Appel, Amsterdam (Ostfildern-Ruit : Cantz Verlag, 1994)
Bassiri, Bizhan ; Fowley, Kim ; Graf, Franz ; Kogler, Peter ; Kopystiansky, Svetlana ; Krystufek, Elke ; Locher, Thomas ; Miyajima, Tatsuo ; Oehlen, Albert ; Rockenschaub, Gerhard ; Tobier, Lincoln ; West, Franz ; Zobernig, Heimo
+ bijlage: illustraties
Jetztzeit, Kunsthalle Wien, 2.9.94 - 23.10.94 ; De Appel, Amsterdam, 25.11.94 - 15.1.95
Duits & Engels
kunstcatalogus